(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
This study examined the relationship between principals’ security safety techniques and effective management of Post Basic Schools in Adamawa State, Nigeria. Three research questions and four hypotheses guided the study. Correlational research design was adopted for this study. The population of this study is 6140. This population comprise of 340 principals’ and 5800 teachers from the five education zones in Adamawa State. This sample for this study is 614. This sample size comprised 580 teachers’ and 34 principals. Multi-stage sampling procedure was adopted for the study. The instrument used for data collection is a self-structured questionnaire titled “Principals’ Security Safety Techniques Questionnaire (PSSTQ)” with a total of 15-items. PSSTQ yielded a reliability co-efficient of 0.80. Descriptive statistics of Mean and Standard Deviation were used in answering the three research questions raised for the study using real limits of numbers. Simple Linear Regression was used in testing hypotheses 1, 2 and 3, while ANOVA of Multiple Regression Analysis was used in testing hypothesis 4 at 0.05 level. The findings revealed that there is a significant relationship between the predictors (physical security management, human security management, technological security management) and effective management of Post Basic Schools, as evidenced by a significant F-statistic (F=5.996, p < .05). It can be concluded that technological security management technique makes the strongest unique contribution to explaining effective management of Post Basic Schools in Adamawa State, Nigeria. Based on the findings of the study, it was recommended among others: principals should endeavor to always use warning signs on perimeter fence, burglar proofing on windows and, protective lighting and other barriers (such as security gate across a passage) as these could further enhance effective school administration. Federal government, State Government and other non-governmental organizations should ensure principals deploy school personnel, parental participation and Rapid Armed Response (Policemen) in combating insecurity in their respective schools by providing them with the necessary manpower requirements and financial support.